Identification of a Potentially Functional circRNA-miRNA-mRNA Regulatory Network in Melanocytes for Investigating Pathogenesis of Vitiligo - Li, Lili; Xie, Zhi; Qian, Xiliang; Wang, Tai; Jiang, Minmin; Qin, Jinglin; Wang, Chen; Wu, Rongqun; Song, Canling (Frontiers in Genetics, 2021)
CircRNAs have been reported to play essential roles in regulating immunity and inflammation, which may be an important regulatory factor in the development of vitiligo. However, the expression profile of circRNAs and their potential biological functions in vitiligo have not been reported so far. In our study we found there are 64 dysregulated circRNAs and 14 dysregulated miRNAs in the patients with vitiligo. Through the correlation analysis, we obtained 12 dysregulated circRNAs and 5 dysregulated miRNAs, forming 48 relationships in the circRNA-miRNA-mRNA regulatory network. Gene Ontology analysis indicated dysregulated circRNAs in vitiligo is closely related to the disorder of the metabolic pathway. The KEGG pathway of dysregulation of circRNAs mainly enriched in the biological processes such as ubiquitin mediated proteolysis, endocytosis and RNA degradation, and in Jak-STAT signaling pathway. Therefore, we found the circRNA-miRNA-mRNA regulatory network are involved in the regulation of numerous melanocyte functions, and these dysregulated circRNAs may closely related to the melanocyte metabolism. Our study provides a theoretical basis for studying the vitiligo pathogenesis from the perspective of circRNA-miRNA-mRNA network.